2015
DOI: 10.1007/s13659-015-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of 4β-Triazole-podophyllotoxin Glycosides

Abstract: A series of novel 4β-triazole-podophyllotoxin glycosides were synthesized by utilizing the Click reaction. Evaluation of cytotoxicity against a panel of five human cancer cell lines (HL-60, SMMC-7721, A-549, MCF-7, SW480) using MTT assay shows that most of these compounds show weak cytotoxicity. It was observed that compound 16 shows the highest activity with IC50 values ranging from 2.85 to 7.28 μM, which is more potent than the control drugs etoposide and cisplatin against four of five cancer cell lines test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
(24 reference statements)
0
3
2
Order By: Relevance
“…Previously, we had reported the cytotoxic activity of 4β-triazole-podophyllotoxin xylosides (all having IC 50 >40 µM against 5 cancer cell lines). 17 However, we have found in this study that per-butyrylation of the xylose residue leads to increased cytotoxic activity. As compounds 10 and 11 do not show in vitro efficacy, we have calculated the ClogP and polar surface area (PSA) values of compounds 8 to 11 by Sybyl, 18 and the data are shown in Table 2.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…Previously, we had reported the cytotoxic activity of 4β-triazole-podophyllotoxin xylosides (all having IC 50 >40 µM against 5 cancer cell lines). 17 However, we have found in this study that per-butyrylation of the xylose residue leads to increased cytotoxic activity. As compounds 10 and 11 do not show in vitro efficacy, we have calculated the ClogP and polar surface area (PSA) values of compounds 8 to 11 by Sybyl, 18 and the data are shown in Table 2.…”
contrasting
confidence: 52%
“…Previously, we had reported the cytotoxic activity of 4β-triazole-podophyllotoxin xylosides (all having IC 50 >40 µM against 5 cancer cell lines). 17 However, we have found in this study that per-butyrylation of the xylose residue leads to increased cytotoxic activity.…”
contrasting
confidence: 52%
“…A number of nucleoside analogues such as Cytarabine, Azacitidine, Capecitabine, Floxuridine, and Decitabine are indeed ratified with antitumor activity [26]. Figure 1 displays a number of reported highly active 1,3,4-thiadiazole and triazole glycosides ( I , III , and IV ) and the triazole–thiadiazole hybrid II against different cancer cells [7,8,9,27,28]. Such significances and our interest in synthesizing new active glycosyl heterocycles [29,30,31,32,33], enhanced our foresight that the 1,3,4-thiazoles and triazoles motif hybrid compounds and their sugar linked products could be useful systems for designing novel cytotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, apart from macromolecular targeted drug development, investigation includes the existing anticancer drug candidates in parallel being tested with the purpose to develop more potent targeted drug molecule. In this context, Hu and co-workers designed a class of 4β-triazolyl-podophyllotoxin glycohybrids via regioselective bridging of clickable terminal alkynes with the azide of podophyllotoxin analogues . The developed analogues were subjected to anticancer evaluation against five human cancer cell lines.…”
Section: Application Of Carbo-cuaac Click Chemistry In Drug Discovery...mentioning
confidence: 99%
“…The resulting molecules were investigated for antibacterial activity against drug-sensitive and drug-resistant strains and demonstrated excellent broad-spectrum activity with improved sensitivity for resistant bacterial strains. Compounds 1149a – c displayed potent activity against sensitive bacterial strains S. aureus and B. subtilis ; on the other hand, compounds 1139d and 1139e (Figure ) showed promising activity for S. pneumoniae . Additional MBC investigation revealed that the compounds 1149a – e were also potent bacteriostatic agents.…”
Section: Application Of Carbo-cuaac Click Chemistry In Drug Discovery...mentioning
confidence: 99%